A 1-V, Low-Power CMOS LNA for Ultra-wideband Receivers - Chang, Po Yang; Wu, Hui-I; Jou, Christina F. (My University, 2007)
A 1-V, low-power ultra-wideband (UWB) low-noise amplifier (LNA) for IEEE 802.153a is implemented in TSMC 0.18-mu m. mixed signal/RF CMOS process. With only 1V bias voltage, the LNA can achieve a measured flat power gain (S21) of 10dB from 2.5 to 8.5 GHz while consuming only 7.25 mW. The minimum noise figure is 3.46dB. A simplified Chebyshev filter is used to achieve an input broadband matching of a measured S11 < -7.1dB from 3.1 to 10.6 GHz. An output-matching buffer is designed specially to match for high gain at upper frequency, the measured S22 is <-12.5dB from 3.1 GHz to 10.6 GHz. Furthermore, the high frequency electromagnetic effect of the transmission lines is considered in this circuit.
Keywords: CMOS; Ultra wide-band; LNA